The effectiveness of marketing mix in stimulating customer satisfaction towards TM Point outlet - Khairi, Nurlina (2006)
The purpose of study is to determine the effectiveness of marketing mix in stimulating customer satisfaction towards TM Point outlet. It also will help the company to identify the best advertising tools in creating customer awareness towards TM Point advertisement. Based on the company, the effectiveness of the marketing mix variables can affect customer satisfaction. In this study, researcher used the primary and secondary data as well to collect the data. Researcher also used the convenience sampling where 70 of respondents are being chosen to answer the questionnaire. The respondents are comprised of the customers that come to the TM Point outlet and have been experienced with the service offered. After collect the data from respondents, the result shows most of them are aware the advertisement of TM Point from television. Researcher also determine that most of the respondents agree about TM Point offered variety of products and services, changed the interior design, offered a reasonable price and used different types of media for promotion activities. This study also help the company to identify the area that they need to improve in order to create customer satisfaction. The recommendations that come from the researcher can be found in this project paper.